2021
DOI: 10.3389/fcvm.2021.748156
|View full text |Cite
|
Sign up to set email alerts
|

Samm50 Promotes Hypertrophy by Regulating Pink1-Dependent Mitophagy Signaling in Neonatal Cardiomyocytes

Abstract: Pathological cardiac hypertrophy, the adaptive response of the myocardium to various pathological stimuli, is one of the primary predictors and predisposing factors of heart failure. However, its molecular mechanisms underlying pathogenesis remain poorly understood. Here, we studied the function of Samm50 in mitophagy during Ang II-induced cardiomyocyte hypertrophy via lentiviruses mediated knockdown and overexpression of Samm50 protein. We first found that Samm50 is a key positive regulator of cardiac hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Excessive activation of autophagy can increase the predisposition to the pathogenesis of myocardial hypertrophy (Qi et al, 2020; C. Song et al, 2021). Xu et al have discovered that Pink1‐Parkin‐mediated mitophagy promotes the development of cardiac hypertrophy (Xu et al, 2021). Notably, autophagy dysfunction can occur in patients with hypertrophic cardiomyopathy and cardiac failure, whereas inhibition of abnormal autophagy could alleviate cardiac left ventricular hypertrophy (Jiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activation of autophagy can increase the predisposition to the pathogenesis of myocardial hypertrophy (Qi et al, 2020; C. Song et al, 2021). Xu et al have discovered that Pink1‐Parkin‐mediated mitophagy promotes the development of cardiac hypertrophy (Xu et al, 2021). Notably, autophagy dysfunction can occur in patients with hypertrophic cardiomyopathy and cardiac failure, whereas inhibition of abnormal autophagy could alleviate cardiac left ventricular hypertrophy (Jiang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Transverse aortic constriction (TAC). Pressure overload was induced by TAC in 9 mice, according to methods we have previously described [ 41 ]. Mice were anesthetized by intraperitoneal injection of a mixture of ketamine (150 mg/kg) and xylazine (10 mg/kg), endotracheally intubated, and ventilated (type 7025, Harvard Apparatus, March-Hugstetten, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al . found that SAMM50 sorting and assembly machinery component (Samm50), a key positive regulator of cardiac hypertrophy, promoted cardiac hypertrophy through regulating Pink1-Parkin-mediated mitophagy [42]. Shirakabe et al .…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%